2023
DOI: 10.1136/bmjpo-2022-001831
|View full text |Cite
|
Sign up to set email alerts
|

Skin-to-skin contact in the delivery room for very preterm infants: a randomised clinical trial

Abstract: ObjectiveEvaluating safety, feasibility and effects on physiological parameters of skin-to-skin contact (SSC) from birth between mothers and very preterm infants in a high-income setting.DesignOpen-label randomised controlled trial.SettingThree Norwegian neonatal units.PatientsPreterm infants at gestational age (GA) 280–316weeks and birth weight >1000g delivered vaginally or by caesarean section (C-section).InterventionTwo hours of early SSC between the mother and the infant compared to standard care (SC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Skin-to-skin contact between the mother and the neonate shortly after birth has been associated with numerous potential health benefits. Several studies have investigated these positive outcomes among preterm neonates in particular, finding associations between skin-to-skin contact and decreased rates of hypothermia [22], improved thermoregulation [23], greater cardiorespiratory stability [24], and decreased dopamine and cortisol levels in this population [25]. Among healthy, full-term infants, a randomized controlled trial of daily skin-to-skin contacts for the first 5 weeks after birth described decreased crying and increased sleep in the infants [26].…”
Section: Skin-to-skin Contactmentioning
confidence: 99%
“…Skin-to-skin contact between the mother and the neonate shortly after birth has been associated with numerous potential health benefits. Several studies have investigated these positive outcomes among preterm neonates in particular, finding associations between skin-to-skin contact and decreased rates of hypothermia [22], improved thermoregulation [23], greater cardiorespiratory stability [24], and decreased dopamine and cortisol levels in this population [25]. Among healthy, full-term infants, a randomized controlled trial of daily skin-to-skin contacts for the first 5 weeks after birth described decreased crying and increased sleep in the infants [26].…”
Section: Skin-to-skin Contactmentioning
confidence: 99%
“…The method, practicalities and techniques do not differ. Second, the term “skin-to-skin contact” is not restricted for all (full-term) newborns, it is widely used for preterm and low birthweight infants ( Forde et al, 2022 ; Kristoffersen et al, 2023 ), including when begun immediately and provided continuously ( Linnér et al, 2022 ). In the Cochrane review it is identified as the primary component of KMC and called “skin-to-skin contact” ( Conde-Agudelo and Díaz-Rossello, 2016 ).…”
Section: New Perspectives On Kmcmentioning
confidence: 99%
“…One of the studies found a positive effect on cardiorespiratory stabilisation 5 as well as normal thermoregulation 6,7 and the other did not find any difference between the groups. 8 Bedetti et al similarly concluded that physiological parameters remain stable when comparing oxygen saturation, heart rate and respiratory rate in preterm infants before and during sessions of SSC. 9 Despite a growing body of evidence supporting early SSC also for preterm infants in high-resource settings, only a minority of EPT and VPT infants were exposed to SSC on their first postnatal day according to a report based on data from the Swedish Neonatal Quality Register (SNQ).…”
mentioning
confidence: 96%